Malnutrition and overall survival in older adults with cancer: A systematic review and meta-analysis. Issue 6 (November 2019) - Zhang, Xiaotao; Tang, Tenglong; Pang, Linda; Sharma, Shreela V.; Li, Ruosha; Nyitray, Alan G.; Edwards, Beatrice J.
Abstract: Background: Some studies have shown that malnutrition is associated with increased risk of mortality in older adults with cancer. However, evidence of its effect is limited and inconsistent. To assess the effect of malnutrition on overall survival in older adults with cancer, we performed a meta-analysis of available studies. Methods: We systematically searched MEDLINE, EMBASE, Web of Science, CINAHL, and PsycINFO for observational studies that examined the association between malnutrition and risk of mortality in older adults with cancer (≥65 years). Malnutrition is defined according to assessment and screening tools in different studies. Older adults with malnutrition were compared with those with normal nutrition for overall survival. A random-effect model was fitted to estimate the summary relative risk (RR) and 95% confidence interval (CI). Between-studies heterogeneity was measured with the I 2 statistic. Results: Ten studies met the inclusion criteria, and a total of 4692 older adults with cancer were included in the meta-analysis. Heterogeneity existed among the different studies ( I 2  = 73.7%, p  < 0.01). Malnutrition was significantly positively associated with increased risk of all-cause mortality (RR: 1.73; 95% CI: 1.23–2.41) compared with those with good nutrition status. A sensitivity analysis of 2773 older adults with cancer on the malnutrition assessed by Mini Nutrition Assessment (MNA), found that malnutrition is still associated with higher risk for all-cause mortality (RR = 2.13, 95% CI: 1.34–3.39). Conclusion: Our meta-analysis of observational studies found a significant effect of malnutrition on overall survival in older adults with cancer.